Enhancing Product Competitiveness at Griya Kerupuk MSMEs Through Packaging Design and Integrated Business Management Information System: Peningkatan Daya Saing Produk Pada UMKM Griya Kerupuk Melalui Desain Kemasan dan Manajemen Bisnis Terintegrasi Sistem Informasi - Sofia Dewi; Ade Iskandar Nasution; Vemy Suci Asih; Lendra Afrizan Musadad (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This community service program was conducted at Griya Kerupuk MSME located in Walini Street, Rancaekek District, Bandung Regency, involving 7 participants consisting of 1 business owner and 6 employees. Griya Kerupuk MSME has promising potential for business development; however, several challenges remain, particularly related to product identity, packaging design, and business management practices that are still relatively simple. This program aimed to improve the partner’s understanding of product branding and more structured business management. The methods employed included observation, interviews, mentoring activities, training sessions, discussions, and questionnaire-based evaluations involving 50 respondents. The mentoring activities focused on logo development, packaging design improvement, and training on simple business record-keeping. The results showed an improvement in the partner’s understanding of the importance of product identity and packaging design in increasing product attractiveness and market value. Evaluation results indicated that 70% of respondents agreed that the new logo was easier to recognize, 72% stated that the packaging information was clearer, 74% agreed that the new packaging increased product value, and 72% stated that simple financial record-keeping helped improve business management. This program is expected to serve as an initial step in strengthening MSME competitiveness through improved product branding and more structured business management.